Factors That Mediate Racial/Ethnic Disparities in US Fetal Death Rates - Lorch, Scott A. (American Public Health Association, 2012)
Objectives. We sought to determine the importance of socioeconomic factors, maternal comorbid conditions, antepartum and intrapartum complications of pregnancy, and fetal factors in mediating racial disparities in fetal deaths. Methods. We undertook a mediation analysis on a retrospective cohort study of hospital-based deliveries with a gestational age between 23 and 44 weeks in California, Missouri, and Pennsylvania from 1993 to 2005 (n = 7 104 674). Results. Among non-Hispanic Black women and Hispanic women, the fetal death rate was higher than among non-Hispanic White women (5.9 and 3.6 per 1000 deliveries, respectively, vs 2.6 per 1000 deliveries; P < .01). For Black women, fetal factors mediated the largest percentage (49.6%; 95% confidence interval [CI] = 42.7, 54.7) of the disparity in fetal deaths, whereas antepartum and intrapartum factors mediated some of the difference in fetal deaths for both Black and Asian women. Among Hispanic women, socioeconomic factors mediated 35.8% of the disparity in fetal deaths (95% CI = 25.8%, 46.2%). Conclusions. The factors that mediate racial/ethnic disparities in fetal death differ depending on the racial/ethnic group. Interventions targeting mediating factors specific to racial/ethnic groups, such as improved access to care, may help reduce US fetal death disparities.